The Development and Transformation of the Bank Card Market as an Imperative for Digitalization: the Case of Central and Eastern European Countries - Olena Sobolieva-Tereshchenko; Olesya Moyseyenko; Valeriia Zharnikova (Comparative Economic Research. Central and Eastern Europe, 2021)
The purpose of this study is to determine the development trends of the major determinants of the bank card market in eight countries of Central and Eastern Europe in the period from 2010 to 2019. Continuing a study carried out in 2018, further comparative analysis of the "Bank Cards Market Index" proposed earlier and based on a system of interrelated indicators of bank payment cards, ATMs and POS-terminals, was carried out. We provide an overview of the rankings of Ukraine, Belarus, Moldova, Russia, Romania, Poland, Hungary, Slovakia using international ranking systems such as "The Legatum Prosperity Index," "Doing Business," "The Index of Economic Freedom," and the "Bank Cards Market Index." Further studies of three international ranking systems, as well as the "Bank Cards Market Index," again confirmed the similarity of the development models of the bank card market in Poland and Ukraine. To study the impact of the digitalization of economics and Covid-19 on the bank card market, a deeper analysis of two cases (Poland and Ukraine, as two similar bank card markets) was carried out using the "Digital Evolution Index." In the course of the research, it was concluded that the "Bank Cards Market Index" can be successfully used for further research of the banking sector of different countries. Also, the growth trend of cashless payments in the bank card market and the possible transformation of the market under the influence of Covid-19, and the global digitalization of economics were noticed. Taking into account the above trend, further studies of the system of interrelated indicators of bank payment cards, ATMs, and POS terminals should be carried out using the "Digital Evolution Index" or other international indexes that characterize the level of digitalization of the economy in the researched countries.
Keywords: G15; G21; O12; 330; bank; Poland; Ukraine; bank cards; indicators; ranking of countries; index; digital economy; digitalization